2019
DOI: 10.1177/0361198119842826
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Traffic Flow Estimation Based on Vehicle-to-Cloud Vehicle Trajectory Data Considering Multi-Intersection Interaction and Coordination

Abstract: Conventional detection methods for intersection traffic flow heavily rely on fixed-location inductive loop, video image processing, infared, and microwave radar detectors. The emerging connected vehicles (CV) technologies can potentially reduce such dependencies on conventional vehicle detectors with the vehicle-to-cloud (V2C) CV data. This paper proposes an analytical method for traffic flow estimation in urban arterial corridors based on CV trajectories collected through V2C communication. Different from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…erefore, the value of J is generally not small. For example, the total research time is only 30 minutes, however, J is generally controlled at [25,35] to meet the constraints of DUE. To sum up, f(O(Δ 1 )) ∈ (0, +∞).…”
Section: E Complexity Of Approximating Dynamic Equilibriummentioning
confidence: 99%
See 1 more Smart Citation
“…erefore, the value of J is generally not small. For example, the total research time is only 30 minutes, however, J is generally controlled at [25,35] to meet the constraints of DUE. To sum up, f(O(Δ 1 )) ∈ (0, +∞).…”
Section: E Complexity Of Approximating Dynamic Equilibriummentioning
confidence: 99%
“…(i) Get the traffic flow of links. An analytical method for traffic flow estimation based on high-resolution vehicle trajectories can be adopted to get the traffic flow of links in the experimental network, seeing literature [35] for details. (ii) Estimate the OD matrix.…”
Section: Experimental Designmentioning
confidence: 99%
“…Only few works have addressed the problem of estimating traffic volume from mobile data sources. Different techniques have been used, such as statistical models [29], [30], [47], combination of Shockwave theory and Maximum likelihood estimation (MLE) [26], [48]- [50], Kalman filter [27], [28], [51], compressive sensing techniques [52], spatio-temporal correlation data-driven models [23], [47], [53], in addition to Flow Diagram-based models where travel speeds from probe vehicle data for each road are estimated and then converted to traffic volumes by exploiting the relationship between travel speeds and traffic volumes [54], [55]. A more complete review can be found in [31].…”
Section: State-of-the-art and Proposed Framework A Review Of Ubimentioning
confidence: 99%
“…Because of these advantages, trajectory data enjoy broad application prospects in performance monitoring, signal control optimization, and other areas (Ban et al, 2011, Chu and Saitou, 2013, Guo et al, 2019, Xu et al, 2018, Ma et al, 2020. A large number of existing methods have been developed for short-term traffic volume estimation (Nanthawichit et al, 2003, Zhan et al, 2017, Duan et al, 2018, Emami et al, 2019, Luo, et al, 2019, Zhang et al, 2020 or cycle-based traffic volume estimation (Zheng and Liu, 2017, Wang et al, 2020, Yao et al, 2020, Zhang et al, 2021. However, critical challenges resulting from low penetration rates (i.e., less than 10% in most cases) and spatiotemporal stochasticity of samples still remain for the use of sampled vehicle trajectory data.…”
Section: Introductionmentioning
confidence: 99%